Spinal Cord Swelling After Surgery in Cervical Spondylotic Myelopathy: Relationship With Intramedullary Gd-DTPA Enhancement on MRI. Issue 7 (August 2018) - Ozawa, Hiroshi; Aizawa, Toshimi; Tateda, Satoshi; Hashimoto, Ko; Kanno, Haruo; Ishizuka, Masato
Abstract : Study Design: This is a prospective multicenter study. Summary of Background Data: Postoperative spinal cord swelling has been reported in patients with cervical spondylotic myelopathy. In the cases of the spinal cord swelling, the involvement in the intramedullary gadoliniumdiethylenetriamine pentaacetic acid (Gd-DTPA) enhancement on magnetic resonance imaging (MRI) was referred. Objective: The prevalence and clinical relevance of postoperative spinal cord swelling and its relationship with intramedullary Gd-DTPA enhancement in patients with cervical spondylotic myelopathy were investigated. Subjects and Methods: A total of 683 consecutive patients with cervical spondylotic myelopathy who underwent laminoplasty were examined. T1, T2, and Gd-DTPA-enhanced MRI were performed before surgery. Patients with intramedullary Gd-DTPA enhancement were allocated to the enhancement group. Fifty consecutive cases who did not exhibit intramedullary Gd-DTPA enhancement were allocated to the nonenhancement group. Both groups underwent MRI examinations at 1 month and 1 year after surgery. Results: The prevalence of spinal cord swelling in the enhancement group (26%) was significantly higher than that in the nonenhancement group (4%) ( P =0.0038). At 1 year after surgery, spinal cord swelling had resolved in all patients in the nonenhancement group, while it persisted in 3 of 13 patients (23%) in the enhancement group. On multiple regression analysis, intramedullary Gd-DTPA enhancement rather than the spinal cord swelling showed a significant influence in terms of recovery of the Japanese Orthopedic Association score. Conclusions: Surgical outcomes of patients with postoperative swelling should be evaluated separately according to the presence or absence of intramedullary Gd-DTPA enhancement on MRI. Spinal cord swelling associated with intramedullary Gd-DTPA enhancement was indicative of poor prognosis.